2018
DOI: 10.3389/fpubh.2018.00061
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Reimbursement Decision-Making Processes in Bulgaria As a Reference Country for the Middle-Income European Countries

Abstract: BackgroundPolicy makers face a lot of challenges in the process of drug reimbursement decision-making, especially in the context of entering the market of more and more innovative medicinal products (MPs). The aim of the current study is to make an overview of the reimbursement system development and to evaluate the access of innovative medicines, which have entered the EU-market in the period 2015–2017, in Bulgaria as reference example for middle-income European country.MethodsA literature and a legislative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The current study revealed a significant variation in the time between market entrance and respective access to different medicines treating a particular rare disease. То some extent, it also confirms the results from a previous study, which revealed that Bulgarian patients have a relatively delayed access to innovative medicines, some of them for rare diseases ( Kamusheva et al, 2018b ), in comparison to other countries. The average time from MA to a reimbursement decision for orphan medicines in Italy, France and Spain is 18.6, 19.5 , and 23.0 months, respectively ( Zamora et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…The current study revealed a significant variation in the time between market entrance and respective access to different medicines treating a particular rare disease. То some extent, it also confirms the results from a previous study, which revealed that Bulgarian patients have a relatively delayed access to innovative medicines, some of them for rare diseases ( Kamusheva et al, 2018b ), in comparison to other countries. The average time from MA to a reimbursement decision for orphan medicines in Italy, France and Spain is 18.6, 19.5 , and 23.0 months, respectively ( Zamora et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…A methodological approach has been developed and published for the inclusion of the medicines in the reimbursement lists as specific clinical and economic criteria are included. A strict economic analysis regarding the financial burden of each disease especially of rare diseases is crucial from both NHIF and patients perspective (22). It was revealed that Bulgarian female patients with acromegaly were almost double than male (127 vs. 64) and those between 41 and 60 years prevailed−45.5%.…”
Section: Discussionmentioning
confidence: 99%
“…17 Similar to our study, a systematic review of cost-effectiveness analyses found that biological therapy should be carefully targeted to specific populations such as responders in order to further improve value. 18 This macro-costing approach possess some limitations because it focuses only on the pharmacotherapy cost and does not include any other costs, due to their unavailability in the country of such an information at central level. [19][20][21][22][23][24][25][26] The other limitation is the lack of data at patient level, as well number of packages sold for the whole period.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have offered explanations for the reasons behind this relatively long procedure for innovative products appraisal in Bulgaria before their inclusion into the PDL. 18 It is also worth commenting that the period for local approval has shortened, allowing for improved access to medicines—from 9 years for omalizmab to 2 years for the others. Factors that might influence the slow penetration of biological anti-asthmatic products on the national market could be the regulatory barriers and companies’ policy for market entrance.13–15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation